2007
DOI: 10.1007/s10654-007-9153-y
|View full text |Cite
|
Sign up to set email alerts
|

Individual-level measures of social capital as predictors of all-cause and cardiovascular mortality: a population-based prospective study of men and women in Finland

Abstract: Individual-level social capital was assessed for prediction of mortality in a nationally representative study population aged 30-99 years at the baseline. A total of 90% of the original sample had participated in a comprehensive health examination (Mini-Finland Health Survey) in 1978-1980. After the first 5 years of the 24-year follow-up period, 1,196 of 3,014 men and 1,280 of 3,689 women died. Individual-level social capital was determined by factor analysis that revealed three factors: residential stability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 32 publications
(62 reference statements)
3
70
1
3
Order By: Relevance
“…These elements foster social cohesion and cooperation with several beneficial outcomes. Research has found that beneficial health outcomes are associated with having trust in others (Fujiwara & Kawachi, 2008;Giordano & Lindström, 2010;Hyyppä et al, 2007;Nieminen et al, 2010;Poortinga, 2006;Snelgrove et al, 2009;Tampubolon et al, 2011), socializing with friends, relatives, colleagues or neighbours (Veenstra, 2000;Ziersch, 2005), and participating in associations (Giordano & Lindström, 2010;Giordano et al, 2011;Hyyppä et al, 2007;Lindström et al, 2004;Nieminen et al, 2010;Poortinga, 2006). However, the evidence for the health benefits of norms of reciprocity and mutual aid is inconclusive (Fujiwara & Kawachi, 2008;Giordano et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These elements foster social cohesion and cooperation with several beneficial outcomes. Research has found that beneficial health outcomes are associated with having trust in others (Fujiwara & Kawachi, 2008;Giordano & Lindström, 2010;Hyyppä et al, 2007;Nieminen et al, 2010;Poortinga, 2006;Snelgrove et al, 2009;Tampubolon et al, 2011), socializing with friends, relatives, colleagues or neighbours (Veenstra, 2000;Ziersch, 2005), and participating in associations (Giordano & Lindström, 2010;Giordano et al, 2011;Hyyppä et al, 2007;Lindström et al, 2004;Nieminen et al, 2010;Poortinga, 2006). However, the evidence for the health benefits of norms of reciprocity and mutual aid is inconclusive (Fujiwara & Kawachi, 2008;Giordano et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, social relations were used at community level. Other studies have used social participation as an indicator for social capital, but at the individual level (Lindström et al 2002;Hyyppä et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…1 for further details on the questions. Social participation is often used as a measure of social capital (Putnam 2000;Lindström et al 2002;Hyyppä et al 2007), whereas the use of other aspects of social relations or combined measures of social relations have, to our knowledge, not earlier been included in measures of social capital. Cattel's ( 2001) study about the mediating role of social networks and social capital shows that some types of social networks facilitate social capital, while other types do not.…”
Section: Bondingmentioning
confidence: 99%
See 1 more Smart Citation
“…Abel (2008) has examined health and health promotion activities especially from the point of view of cultural capital [20]. In earlier studies social capital, as one form of capital, has been defined as wide welfare-related effects in the promotion of the health and well-being of adults, children and adolescents [22,24,25], so it is justified to adapt the theory of social capital also in the well-being and health of school communities. In this article we focus on social capital from the point of view of social support networks and partnership as the resources of the school community's and pupils' health and well-being by applying Abel's model of the forms of capital and contextualizing it in the school community (Fig.…”
Section: Partnership and The Social Support Network As The Resourcesmentioning
confidence: 99%